CNTNAP4 Impacts Epilepsy Through GABAA Receptors Regulation: Evidence From Temporal Lobe Epilepsy Patients and Mouse Models. (22nd August 2017) - Shangguan, Yafei; Xu, Xin; Ganbat, Baigalimaa; Li, Yun; Wang, Wei; Yang, Yong; Lu, Xi; Du, Chao; Tian, Xin; Wang, Xuefeng
Abstract: Epilepsy is a serious neurological condition characterized by recurrent unprovoked seizures. The exact etiology of epilepsy is not fully understood. Here, we demonstrated that the expression of contactin-associated protein-like 4 (CNTNAP4) was decreased in the temporal neocortex of epileptic patients and in the hippocampus and cortex of epileptic mice. Lentivirus-mediated knock-down of CNTNAP4 in the hippocampus increased mice susceptibility to epilepsy. Conversely, lentivirus-mediated overexpression of CNTNAP4 decreased epileptic behavior in mice. CNTNAP4 affected neuronal excitability and inhibitory synaptic transmission via postsynaptic receptors in Mg 2+ -free epilepsy cell model. Down-regulation or overexpression of CNTNAP4 in the hippocampus influenced the expression of gamma-aminobutyric acid A receptor β2/3 (GABAA Rβ2/3) membrane protein, without affecting total GABAA Rβ2/3 protein concentration in epileptic mice. Protein interactions between CNTNAP4, GABAA Rβ2/3 and gamma-aminobutyric acid receptor-associated protein (GABARAP) were observed in the hippocampus of epileptic mice. These findings suggest CNTNAP4 may be involved in the occurrence and development of epilepsy through the regulation of GABAA R function, and may be a promising target for the development of epilepsy treatment.